Knowing, Not-Knowing, and Jouissance Levels, Symbols, and Codes of Experience in Psychoanalysis - Moncayo, Raul (The Palgrave Lacan Series, 2018)
This book explores the practice and transmission of Lacanian and Freudian theory. It discusses the pure versus applied analysis of Lacanian and Freudian theory in practice; and the hierarchical versus circular transmissions within psychoanalytic organizations. Underpinned by extensive practical knowledge of the clinic, this work examines the differences between Freud and Lacan in their understanding of the subject and the unconscious and pushes them in new directions. The book also offers an analysis and commentary of several key Lacanian texts including an accessible study of the notoriously challenging text L'etourdit. Offering both divergent and reinforcing takes on Lacan, the author explores the traits that separate out the psychoanalyst from other twentieth-century thinkers and theorists. This book offers a clear clinical picture of where Lacanian psychoanalysis is today, both in the US and internationally.